2019
DOI: 10.1159/000495787
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Beta Treatment Differentially Alters TLR2 and TLR4-Dependent Cytokine Production in Multiple Sclerosis Patients

Abstract: Objective: Multiple sclerosis (MS) is a multifactorial chronic disease that affects the central nervous system (CNS). Toll-like receptors (TLRs) play a central role in cytokine production after pathogen- and danger-associated molecular patterns (PAMPs and DAMPs) and contribute to CNS damage in MS patients. Here, we evaluated the effects of interferon (IFN)-β treatment in TLR2 and TLR4-dependent cytokine production and mRNA expression in whole-blood cell cultures from MS patients. Methods: We evaluated cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The small sample of veterans with MS was being treated for MS using various disease modifying therapies (DMTs). Various treatment regimens, designed to modulate the immune system, have the potential to alter proinflammatory and anti-inflammatory cytokines (Oliveira et al, 2019;Williamson et al, 2012). The relationship identified between the inflammatory marker cytokines and depression severity in this cross-sectional study may not be true for longitudinal trends.…”
Section: Limitationsmentioning
confidence: 82%
“…The small sample of veterans with MS was being treated for MS using various disease modifying therapies (DMTs). Various treatment regimens, designed to modulate the immune system, have the potential to alter proinflammatory and anti-inflammatory cytokines (Oliveira et al, 2019;Williamson et al, 2012). The relationship identified between the inflammatory marker cytokines and depression severity in this cross-sectional study may not be true for longitudinal trends.…”
Section: Limitationsmentioning
confidence: 82%
“…12 It has been demonstrated that activation of TLR2 and TLR4 in dentritic cells or macrophages can indirectly promote leukocyte invasion via the blood-brain barrier and contribute to CNS damage in patients with MS. 13,14 The production of pro-and anti-inflammatory cytokines is induced by stimulation of TLRs. 15,16 The elevated level of TLR2 and TLR4 expression is one form of evidences that supports this thought in patients with MS and EAE, an animal model for MS. [17][18][19] β-D-mannuronic acid (M2000) is a small molecule (patent number: DE/102016113018.4-PCT/ EP2017/067919) with anti-inflammatory properties and low molecular weight, that has not caused any toxicity on bone marrow, kidney, and liver. The hematological, biochemical, and urinalysis findings in the M2000 group did not show any treatment-related adverse effects.…”
mentioning
confidence: 78%
“…It has been demonstrated that activation of TLR2 and TLR4 in dentritic cells or macrophages can indirectly promote leukocyte invasion via the blood‐brain barrier and contribute to CNS damage in patients with MS 13,14 . The production of pro‐ and anti‐inflammatory cytokines is induced by stimulation of TLRs 15,16 . The elevated level of TLR2 and TLR4 expression is one form of evidences that supports this thought in patients with MS and EAE, an animal model for MS 17–19 …”
mentioning
confidence: 89%
“…The effect of different disease-modifying therapies (DMTs) may be mediated by the modulation of the inflammatory milieu. Treatment with IFN-B in MS is associated with reduced production of TNF compared to untreated patients [ 34 ], decreased RANTES levels [ 28 ], and increased IL-10 release in blood cell cultures [ 35 ]. Treatment with cladribine has been associated with a reduced relapse rate and decreased progression of disability [ 36 ].…”
Section: Discussionmentioning
confidence: 99%